Exploring the Social Context of Instrumental and Expressive Homicides: An Application of Qualitative Comparative Analysis - Miethe, Terance D. (Journal of quantitative criminology, 1999)
Using data from the UCR's Supplementary Homicide Reports, the methodof qualitative comparative analysis (QCA) is used to examine whetherinstrumental and expressive homicides are similar or unique in their socialcontext (i.e., combinations of offender, victim, and situationalcharacteristics). Instrumental and expressive homicides are found to haveboth common and unique social contexts, but the vast majority of homicideincidents involve combinations of individual and situational factors thatare common in both general types of homicides. Among subtypes ofinstrumental (like rape, prostitution, robbery murders) and expressivehomicides (like lovers' triangles, brawls, and arguments), there iswide variability in their prevalence of unique and common components. Afterdiscussing these results, the paper concludes with illustrations of how QCAmay be used in other areas within criminology.